Case report: SCN4A p.R1135H gene variant in combination with thyrotoxicosis causing hypokalemic periodic paralysis - Zhang, Zhi; Xiao, Banghui (Frontiers in Neurology, 2023)
Hypokalemic periodic paralysis (HPP) is a heterogeneous group of diseases characterized by intermittent episodes of delayed paralysis of skeletal muscle with episodes of hypokalemia, caused by variants in CACNA1S or SCN4A genes, or secondary to thyrotoxicosis, Sjogren syndrome, primary aldosteronism etc. HPP may be the only presentation in Andersen-Tawil syndrome which the majority of cases are caused by pathogenic variants in the KCNJ2 gene. We present a case of a 29-year-old male with hypokalemic periodic paralysis. The patient began to experience recurrent weakness of the extremities at the age of 26, which were effectively treated with potassium supplementation. He had recently developed dry mouth, palpitations, weight loss, and even dyspnea, with a serum potassium level as low as 1.59mmol/L. The results of auxiliary examinations showed Graves’ disease, and genetic testing indicated a missense variant, NM_000334.4(SCN4A):c.3404G>A (p.R1135H). He did not experience periodic paralysis during follow-up after lifestyle guidance and treatment of thyrotoxicosis with radioactive iodine. It is a rare case of SCN4A p.R1135H gene variant combined with hyperthyroidism resulting in hypokalemic periodic paralysis with respiratory muscle paralysis to raise awareness of the disease and avoid misdiagnosis and missed diagnosis.